Homozygous GDF2 nonsense mutations result in a loss of circulating BMP9 and BMP10 and are associated with either PAH or an "HHT‐like" syndrome in children. Issue 12 (9th April 2021) - Hodgson, Joshua; Ruiz‐Llorente, Lidia; McDonald, Jamie; Quarrell, Oliver; Ugonna, Kelechi; Bentham, James; Mason, Rebecca; Martin, Jennifer; Moore, David; Bergstrom, Katie; Bayrak‐Toydemir, Pinar; Wooderchak‐Donahue, Whitney; et al.
Abstract: Background: Disrupted endothelial BMP9/10 signaling may contribute to the pathophysiology of both hereditary hemorrhagic telangiectasia (HHT) and pulmonary arterial hypertension (PAH), yet loss of circulating BMP9 has not been confirmed in individuals with ultra‐rare homozygous GDF2 (BMP9 gene) nonsense mutations. We studied two pediatric patients homozygous for GDF2 (BMP9 gene) nonsense mutations: one with PAH (c.[76C>T];[76C>T] or p.[Gln26Ter];[Gln26Ter] and a new individual with pulmonary arteriovenous malformations (PAVMs; c.[835G>T];[835G>T] or p.[Glu279Ter];[Glu279Ter]); both with facial telangiectases. Methods: Plasma samples were assayed for BMP9 and BMP10 by ELISA. In parallel, serum BMP activity was assayed using an endothelial BRE‐luciferase reporter cell line (HMEC1‐BRE). Proteins were expressed for assessment of secretion and processing. Results: Plasma levels of both BMP9 and BMP10 were undetectable in the two homozygous index cases and this corresponded to low serum‐derived endothelial BMP activity in the patients. Measured BMP9 and BMP10 levels were reduced in the asymptomatic heterozygous p.[Glu279Ter] parents, but serum activity was normal. Although expression studies suggested alternate translation can be initiated at Met57 in the p.[Gln26Ter] mutant, this does not result in secretion of functional BMP9. Conclusion: Collectively, these data show that homozygous GDF2 mutations, leading to a loss of circulating BMP9 and BMP10, can cause either pediatric PAH and/or "HHT‐like" telangiectases and PAVMs. Although patients reported to date have manifestations that overlap with those of HHT, none meet the Curaçao criteria for HHT and seem distinct from HHT in terms of the location and appearance of telangiectases, and a tendency for tiny, diffuse PAVMs. Abstract : Ultra‐rare homozygous GDF2 mutations have not previously been shown to lead to loss of circulating BMP9 protein. We show that homozygous GDF2 mutations in two pediatric individuals from two different families, lead to loss of plasma BMP9 and BMP10, resulting in a loss of serum‐derived BMP‐dependent endothelial signaling. The two individuals have different vascular dysplasias: one with pulmonary arterial hypertension and the second with a pulmonary arteriovenous and telangiectasia syndrome that is distinct from hereditary hemorrhagic telangiectasia but may be mistakenly diagnosed as hereditary hemorrhagic telangiectasia.